Formules omvormen

Hoofdmenu Eentje per keer 

Vorm de formules om

  1. \(\text{Vorm de formule } N = T q - s \text{ om naar de variabele } T\)
  2. \(\text{Vorm de formule } T = \dfrac{(P+H)x}{9} \text{ om naar de variabele } x\)
  3. \(\text{Vorm de formule } H^2 = \rho^2 + P^2 \text{ om naar de variabele } P\)
  4. \(\text{Vorm de formule } c=Q \cdot P \text{ om naar de variabele } Q\)
  5. \(\text{Vorm de formule } s=R \cdot b \text{ om naar de variabele } R\)
  6. \(\text{Vorm de formule } \omega = 5 (x R + c) \text{ om naar de variabele } R\)
  7. \(\text{Vorm de formule } q = \delta Q + \rho \text{ om naar de variabele } Q\)
  8. \(\text{Vorm de formule } \delta = 6 (\rho \psi + H) \text{ om naar de variabele } \psi\)
  9. \(\text{Vorm de formule } \psi = \phi y^2 \text{ om naar de variabele } \phi\)
  10. \(\text{Vorm de formule } s=T - x \text{ om naar de variabele } x\)
  11. \(\text{Vorm de formule } P = \dfrac{c}{R \delta} \text{ om naar de variabele } c\)
  12. \(\text{Vorm de formule } c = \psi Q^2 \text{ om naar de variabele } \psi\)

Vorm de formules om

Verbetersleutel

  1. \( \color{red}{N = T q - s} \\ \Leftrightarrow N+s = T \cdot q \\ \Leftrightarrow \dfrac{N+s}{q} = T\)
  2. \( \color{red}{T = \dfrac{(P+H)x}{9}} \\ \Leftrightarrow 9 \cdot T = (P + H ) x \\ \Leftrightarrow \dfrac{9 \cdot T}{P + H} = x\)
  3. \( \color{red}{H^2 = \rho^2 + P^2} \\ \Leftrightarrow H^2 - \rho^2 = P^2 \\ \Leftrightarrow \sqrt{H^2 - \rho^2} = P \\\)
  4. \( \color{red}{c=Q \cdot P} \\ \Leftrightarrow Q=\dfrac{c}{P}\)
  5. \( \color{red}{s=R \cdot b} \\ \Leftrightarrow R=\dfrac{s}{b}\)
  6. \( \color{red}{\omega = 5 (x R + c)} \\ \Leftrightarrow \omega = 5 \cdot x \cdot R + 5 \cdot c \\ \Leftrightarrow \omega- 5 \cdot c = 5 \cdot x \cdot R \\ \Leftrightarrow \dfrac{\omega- 5 \cdot c}{5 \cdot x} = R\)
  7. \( \color{red}{q = \delta Q + \rho} \\ \Leftrightarrow q-\rho = \delta \cdot Q \\ \Leftrightarrow \dfrac{q-\rho}{\delta} = Q\)
  8. \( \color{red}{\delta = 6 (\rho \psi + H)} \\ \Leftrightarrow \delta = 6 \cdot \rho \cdot \psi + 6 \cdot H \\ \Leftrightarrow \delta- 6 \cdot H = 6 \cdot \rho \cdot \psi \\ \Leftrightarrow \dfrac{\delta- 6 \cdot H}{6 \cdot \rho} = \psi\)
  9. \( \color{red}{\psi = \phi y^2} \\ \Leftrightarrow \dfrac{\psi}{y^2} = \phi\)
  10. \( \color{red}{s=T - x} \\ \Leftrightarrow s-T = -x \\ \Leftrightarrow -s+T = x\)
  11. \( \color{red}{P = \dfrac{c}{R \delta}} \\ \Leftrightarrow P \cdot R \cdot \delta = c\)
  12. \( \color{red}{c = \psi Q^2} \\ \Leftrightarrow \dfrac{c}{Q^2} = \psi\)
Oefeningengenerator vanhoeckes.be/wiskunde 2021-12-02 01:45:17